SOSIALISASI DAN EDUKASI PENGELOLAAN SAMPAH DI DESA PEMECUTAN KAJA - Ida Ayu Putu Sri Mahapatni; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2026)
Sustainable waste management is key to reducing negative impacts on the environment. Waste management socialization and education are a form of community service carried out by the Hindu University of Indonesia through the Thematic Community Service Program (KKN)